Final year student research symposium - Husain, Noreen; Ali, Aida Azlina (Faculty of Pharmacy, 2025)
On 11 July 2025, the Faculty of Pharmacy hosted the Final Year Student Research Symposium, bringing together 180 students at Student Activity Rooms 1 and 2, and Lecture Hall 9. The poster presentations offered final-year students the opportunity to showcase their research findings, fulfilling an essential academic requirement while gaining valuable experience in professional scientific communication. Beyond highlighting research outcomes, the symposium fostered the exchange of ideas, encouraged networking with peers and evaluators, and included a special interactive session with 27 international guest students from the Faculty of Pharmacy, Universitas Airlangga, Surabaya, Indonesia. The event also allowed the academic community to appreciate students’ research potential and to identify high-impact projects with promising avenues for publication and innovation.